Et Al Alastair Marriot, Frederick Ashton and Kenneth MacMillan - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2006)
Alastair Marriot, Frederick Ashton and Kenneth MacMillan sharing the Convent Garden stage. PALABRAS CLAVE: Alastair Marriot, Frederick Ashton, Kenneth MacMillan.